PENERAPAN MASSAGE EFFLEURAGE TERHADAP NYERI PUNGGUNG IBU HAMIL TRIMESTER III DI PUSKESMAS TANJUNG BALAI KARIMUN - Muti Qurnia; Arum Dwi Anjani (Universitas Batam, 2023)
Back pain is one of the most common discomforts felt by third trimester pregnant women during pregnancy. Back pain occurs in 60% to 90% of pregnant women. Non-pharmacological methods, namely by several ways to reduce the frequency of low back pain, among others, with Effleurage massage. Research Objectives Provide midwifery care to pregnant women by applying massage effleurage to reduce back pain. The type of research used in the preparation of practice reports is descriptive research using the case study method. The research was conducted at the Tanjung Balai Karimun Health Center in March 2023. The subjects used in this case study were third trimester pregnant women with back pain problems. Data collection methods are participatory observation, interviews, measurements, documentation. The research instruments were midwifery care format, SOP Massage Effleurage and pain measurement instrument (NRS). After reviewing the case and evaluating the case, there is no gap between theory and practice in the field. Effleurage massage can reduce back pain in third trimester pregnant women. For mothers, it is hoped that they will receive midwifery care during pregnancy according to their needs and increase their knowledge about the services they have received